Research on ultrasonic phased array detection algorithm for TA15/Ti2AlNb multi-layer gradient material structure - Li, Wentao; Zhang, Wenbin; Yang, Gongpeng (Applied acoustics, 2023)
•A new algorithm for solving the ultrasonic beam propagation refraction path of multi-layer gradient material structure is proposed.•A TA15/Ti2AlNb gradient material specimen was prepared using LMD technology.•Establishing the gradient material multilayer structure simulation model with the FDTD method to verify the focusing law.•A algorithm results in a lower detection SNR and improved detection quality. Conventional ultrasonic detection methods can detect a TA15/Ti2AlNb gradient material multi-layer structure with many layers; the reflection and refraction phenomena of ultrasonic waves at the partition interface result in considerable attenuation of ultrasonic energy. It is difficult to achieve accurate focusing control of multi-array element synthetic beams, and internal defects cannot be detected. We explored the ‘ultrasonic velocity scale coefficient K’ algorithm to determine the ultrasonic beam propagation refraction path of a multi-layer gradient material structure. The algorithm makes full use of the refraction characteristics of ultrasonic waves on each material layer interface, establishes the acoustic ray-tracing model, analyzes the acoustic ray-tracing propagation path of each array element, and quickly obtains the focusing law. A TA15/Ti2AlNb gradient material specimen was prepared using laser melting deposition (LMD) technology, and a multi-layer structure model was established based on the finite difference time domain (FDTD) method to verify the focusing law. The experimental results of the ultrasonic phased array showed that the proposed algorithm effectively improved the defect detection signal-to-noise ratio (SNR) and imaging quality of the TA15/Ti2AlNb gradient material.